Month 60 Imaging Findings and Relationship to Treatment Outcomes Following Anti-VEGF Therapy for Macular Edema Due to Central or Hemi-Retinal Vein Occlusion - Ip, Michael S.; Scott, Ingrid U.; VanVeldhuisen, Paul C.; Oden, Neal L.; Blodi, Barbara A. (American journal of ophthalmology, 2024)
To evaluate imaging findings from SCORE2 participants through 60 months, to describe the degree of resolution or progression of these variables, and to correlate changes in these imaging findings to treatment outcomes such as visual acuity and the number of treatments administered. SCORE2 participants were followed for up to 60 months. Visual acuity, injection frequency and imaging tests color fundus photography (CFP), optical coherence tomography (OCT), and ultra-widefield fluorescein angiography [UWFA]) were performed throughout this period. Less than 6% of eyes had subretinal fluid at month 60. Disorganization of the retinal inner layers (DRIL) was the most likely finding to persist, present in 96% of eyes at baseline and unchanged at 95% at month 60. For UWFA, at baseline, there was a mean of 5.0% non-perfusion area (95% CI: 3.3%-6.8%) in the NETWORC grid with little change to month 60. For the Early Treatment Diabetic Retinopathy Study (ETDRS) grid, at baseline, there was a mean of 2.3% non-perfusion area (95% CI: 0.7%-3.9%) with little change to month 60. There was no correlation between any of the imaging variables at baseline and change in visual acuity to month 60 or in the number of injections following the variable treatment timeframe (month 12 to month 60). These analyses provide an anatomic explanation for persistent functional deficits many years following initial treatment. Clinical practice patterns should consider evaluation with these imaging tests to help explain persistent functional deficits in many eyes. Additionally, these 8 baseline imaging variables generally should not be relied on to predict visual acuity or intensity of treatment. NOTE: Publication of this article is sponsored by the American Ophthalmological Society.